The population policy of the Russian Far East - Yu. A. Avdeev (Статистика и экономика, 2018)
The purpose of the study: identify the current demographic situation in the Russian Far East over the past quarter century, to assess the effectiveness of those efforts at the federal and local levels, to identify problems and propose the sequence of their decision for the following discussion. Materials and methods. The initiative of the Ministry for the Development of the Russian Far East to develop a regional concept of the demographic policy, three scientific conferences on demographic development of the region (2015, 2016 and 2017 respectively), approved by the Government Decree the Concept of the Demographic Development of the Far East (from June 20, 2017 № 1298-r), on the one hand, give hope that the demographic catastrophe will be prevented in this part of the country, but on the other hand, there is a fear that the adopted document, a set of follow-up actions will not significantly alter steady demographic trend, as dozens of previous decisions could not do this. Therefore, a further search of non-usual steps for the impact on the demographic potential of the region is necessary. The results. Analysis of population structure by age and sex, their differentiation by territories show: relatively small generation of 90- ies, entering into the fertile age, leads to a decrease in the birth rate, which inevitably effect on the total population. This requires adjusting the choice of priorities of a demographic policy. Typological characteristics of the demographic behavior of the regions of the Federation, formed under the influence of natural and geographical conditions and the way of life of the population, are mandatory in the regional demographic policy. It is not enough to understand the need to improve the quality of life and create attractive conditions for migrants. Peculiarities of territorial organization of economy and population, with the population density (when a person per square km), also significantly affect the formation of social and infrastructure complex. Self-organization processes occur independently from decisions, made in the power structures: shift method of organization of production becomes predominant for the areas with extreme climatic conditions, whereas the South of the Far East could become a foothold for ongoing family life for those who work in the North. Crucial issue of the regional demographic policy is the prospect of economic specialization: it is one thing when the rate is made on resource development and export of raw materials, and the other is industrial development, requiring highly qualified personnel, appropriate infrastructure, development of service industries, etc. Raising the level of migration attractiveness of territory applies to the investments, capital, not only to people. It is important to assess the severity of the demographic problems of the region, the critical state that does not allow you to make a mistake. Conclusion. Announcing Far East a priority for century, creating special conditions for business, population growth should be commensurate with the scale of the projects claimed, moreover, this growth must be faster, which is possible only through migration from the outside. In the coming decade efforts should be focused on the revitalization of the migratory processes, and ensure the growth of the population of the territory.